The specifics of supply chain of medical kits product group in the context of using Enterprise Resource Planning class systems - Sylwester Bejger (Ekonomia i Prawo, 2016)
Motivation: The article contains proposals of IT solutions supporting the management of selected links in the supply chain of Disposable Medical Kits product group. Aim: The aim of the article is the analysis of the distinctive features of the supply chain of Disposable Medical Kits product group (later referred to as DMK) in the context of managing such chain by means of IT solutions. Results: The first part of the article identifies distinctive features of the supply chain for this product group, which are of importance in the context of realizing the goals of social logistics of medical products supplies, as well as from the point of view of optimizing the management of the chain’s individual links. The second part of the article is devoted to presenting proposals of IT solutions supporting the management of supply chain, whose functionality are implied by the analysis conducted in the first part.